Nursing consultation in the Family Health Strategy and the nurse's perception: Grounded Theory - Silva E Lima, Stella Godoy [UNESP]; Spagnuolo, Regina Stella [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Colichi, Rosana Maria Barreto [UNESP] (My University, 2022)
OBJECTIVES: to understand the experience of nurses with nursing consultations in the context of the Family Health Strategy and propose a representative model. METHODS: qualitative research using Grounded Theory, with 14 nurses working through non-directive interviews. For data analysis, three stages were used: open, axial and selective coding, which originated phenomena, themes, categories and subcategories, which supported the construction of the central category and, consequently, the theoretical model. RESULTS: the interrelation of phenomena emerged from the essence of the nurse's experience, revealing the central category: From nursing education to the practice of Nursing Consultation, unveiling learning, challenges and autonomy as intervening components. Final Considerations: the nurse's experience is positive and, despite numerous challenges in daily life, the nurse has been performing it based on comprehensive care. New studies may add new understandings that enable the expansion of working conditions, valuing the nursing consultation.